PENGARUH INFLASI, SUKU BUNGA SBI , DAN KURS TERHADAP INDEKS HARGA SAHAM GABUNGAN - Kurnia Sari Dewi (Unversitas Prof. Dr. Moestopo (Beragama), 2022)
The aim to be achieved in the preparation of this research is to determine the effect of inflation, SBI interest rates, and exchange rates on the Jakarta Composite Index (IHSG). The research method used is ex post facto. And the sample method used is purposive sampling with several predetermined criteria. The research sample consisted of 60 observational data listed on the Indonesia Stock Exchange for the period 2016 to 2020. The analysis technique used was multiple regression equations and hypothesis testing using the t test and F test with a significance level of 5%. The results of this study indicate that inflation and SBI interest rates partially (each) have no significant effect on the JCI, while the exchange rate has a significant and simultaneously (together) inflation, SBI interest rates and exchange rates have a significant effect on the IHSG on the Indonesia Stock Exchange from 2016 to 2020. The significant multiple effect is 32.2%, while the remaining 67.8% is influenced by other factors outside the research.